+0  
 
0
50
1
avatar+467 

\(\begin{align*} x + 3y + 2z &= 1,\\ -3x + y + 5z &= 10,\\ -2x - 3y +z &= 7. \end{align*}\)

 Nov 30, 2020
 #1
avatar+114592 
+1

x + 3y + 2z   = 1        (1)

-3x+ y + 5z   =10       (2)

-2x -3y + z   = 7         (3)

 

Adding (1)  and (3)   we get

-x +3z   = 8      (4)

 

Multiply  (2)  by  3  =   -9x + 3y  + 15z    = 30

Add this to    (3)    and we  get

-11x + 16z  = 37    (5)

 

Multiply   (4)  by -11   and we  get      11x  - 33z = -88

Add this  to  (5)  and we  get that

-17z  = - 51

z = -51/-17   =  3

 

Sub yhis into (4)  to find  x

-x + 3(3)  = 8

9 - 8  = x

1   = x 

 

And using (1) to find y

 

1 + 3y + 2(3)  = 1

3y + 6  =0

3y  =  -6

y = -6/3

y  = -2

 

{ x, y, z }  =   { 1, -2, 3 }

 

 

cool cool cool

 Nov 30, 2020

45 Online Users

avatar